A comparative study of perceptions of student-athletes and normal stream students towards the learning of english literature / Noreen Amira Zakaria - Zakaria, Noreen Amira (2014)
This research was carried out to investigate the perceptions of student-athletes and normal stream students towards the learning of the English literature. The purpose of this study was to investigate secondary school students’ perceptions towards the relevance of learning literature in ESL classroom. This study compared the perceptions between student-athletes and normal stream students. The samples used in this study were 60 students - 31 student-athletes and 29 normal stream students. A set of questionnaire were distributed to them in order to gain the information needed. An interview was also conducted with the respective English teacher to support the results of the questionnaire. Based on the findings, the students generally have a good perceptions towards the learning of English literature but often find poetry as the most challenging texts.